Implementasi Kitab “Hayya Nata’allamil ‘Arobiyyah” Pada Pembelajaran Mufrodat Siswi Kelas IISD di Kuttab Shalahuddin Al-Ayyubi Karanganyar - Lina Mufidatu Roidah (Thulabuna: Jurnal Pendidikan Bahasa Arab, 2022)
This study aims to examine the implementation of the Hayya Nata’allamil ‘Arobiyyah book in mufrodat (vocabulary) learning at Kuttab Shalahuddin Al-Ayyubi Karanganyar, as well as to identify the outcomes and the supporting and inhibiting factors of its implementation. This research uses a qualitative descriptive method. To complete the data collection, techniques such as observation, interviews, and documentation were employed. The results of the study show that 100% of the female students reached the minimum competency standard (KKM) set by the kuttab. The supporting factors for the implementation of the Hayya Nata’allamil ‘Arobiyyah book in vocabulary learning at Kuttab Shalahuddin Al-Ayyubi Karanganyar include adequate facilities, professional teaching staff, and strong student motivation. On the other hand, the inhibiting factors are the students’ educational backgrounds, the time allocated for Arabic language lessons, and the varying levels of student ability.